Values as a result of the God-man and business conduct - Santos Gutierrez, Edual Delmar (2016)
The goal of this review is to highlight the importance of the values that are built as a result of the relationship between God and man. Values are experiences that come from multiple sources, and can be objectives and subjectives. This creates an oppressive social thought of dominant values, accepted by the cultural demand with which one could not be identified. The experienced values under the domination of individualism deconstructed the civilization, because the human being is not autonomous or a lonely creation. His being reason is the community. The business behavior survives in the society, therefore requires strong links and these are only found in the man's relationship with God.